2019
DOI: 10.3389/fphar.2019.00339
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System as a Target in Cancer Diseases: Are We There Yet?

Abstract: The endocannabinoid system (ECS) has been placed in the anti-cancer spotlight in the last decade. The immense data load published on its dual role in both tumorigenesis and inhibition of tumor growth and metastatic spread has transformed the cannabinoid receptors CB1 (CB1R) and CB2 (CB2R), and other members of the endocannabinoid-like system, into attractive new targets for the treatment of various cancer subtypes. Although the clinical use of cannabinoids has been extensively documented in the palliative sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
151
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(152 citation statements)
references
References 304 publications
(386 reference statements)
0
151
0
1
Order By: Relevance
“…The endocannabinoid system also includes endogenously synthesised ligands for these receptors (anandamide and 2‐arachidonoylglycerol), and enzymes and transporters to control their synthesis (from membrane phospholipids) and degradation (Lu & Mackie ; Moreno et al . ). While CB 1 receptors are most highly expressed in the central and peripheral nervous system and are primarily responsible for the psychoactive effects of THC, CB 2 receptors are mainly found on immune cells, although also in the brain, and their activation is associated with immunomodulatory effects (Cabral et al .…”
Section: Pharmacology Of Cbdmentioning
confidence: 97%
See 1 more Smart Citation
“…The endocannabinoid system also includes endogenously synthesised ligands for these receptors (anandamide and 2‐arachidonoylglycerol), and enzymes and transporters to control their synthesis (from membrane phospholipids) and degradation (Lu & Mackie ; Moreno et al . ). While CB 1 receptors are most highly expressed in the central and peripheral nervous system and are primarily responsible for the psychoactive effects of THC, CB 2 receptors are mainly found on immune cells, although also in the brain, and their activation is associated with immunomodulatory effects (Cabral et al .…”
Section: Pharmacology Of Cbdmentioning
confidence: 97%
“…The CB 1 and CB 2 receptors are members of the G proteincoupled receptor family and form one component of the endocannabinoid signalling system, which also includes other types of receptors, such as transient receptor potential ion channels and the nuclear peroxisome proliferator-activated receptor gamma (PPARc). The endocannabinoid system also includes endogenously synthesised ligands for these receptors (anandamide and 2-arachidonoylglycerol), and enzymes and transporters to control their synthesis (from membrane phospholipids) and degradation (Lu & Mackie 2016;Moreno et al 2019). While CB 1 receptors are most highly expressed in the central and peripheral nervous system and are primarily responsible for the psychoactive effects of THC, CB 2 receptors are mainly found on immune cells, although also in the brain, and their activation is associated with immunomodulatory effects (Cabral et al 2015).…”
Section: Pharmacology Of Cbdmentioning
confidence: 99%
“…Concerning to CB2R agonists, among phytocannabinoid, morin, a flavonoid structurally closely related to quercetin, showed an apoptotic effect by a mechanism not fully resolved [10]. Interestingly, synthetic compounds as WIN55,212-2, JWH-015, JWH-133 were found able to induce cannabinoid receptor dependent anti-proliferative and pro-apoptotic effects both in vitro and in vivo assays [7,[11][12][13][14][15]. Recently, researchers have discovered the ability of CB2R to form heteromers with other GPCRs, as CXCR4 or GPR55.…”
Section: Editorialmentioning
confidence: 99%
“…Recently, researchers have discovered the ability of CB2R to form heteromers with other GPCRs, as CXCR4 or GPR55. For instance, in human breast and prostate cancer cells, the G protein-coupled chemokine receptor CXCR4, physiologically responsible for cell proliferation and migration, associated to CB2R yields the functional heteromers CXCR4-CB2R, which leads to a decrease of cancer spread [14].…”
Section: Editorialmentioning
confidence: 99%
“…It has been demonstrated that the ECS is functionally expressed in the human bladder [9] and that its regulation is implicated in lower urinary tract function and dysfunction [10]. Moreover, recent literature strongly suggests a role for the ECS in the pathogenesis of cancer [11,12], describing the involvement of ECs and NAEs in maintaining balance in cell proliferation. It has been shown successfully that ECs can act by several different cellular mechanisms, including inhibition of cell proliferation, migration and progression; inhibition of angiogenesis; and promotion of apoptosis and/or cell cycle arrest [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%